I’JAZ AL-BAYANI DALAM USLUB AL-QUR’AN :HAMZAH ISTIFHAM DALAM AL- QUR’AN - Fadhilah Umami; Rajab Al Fathin Nasution, Harun Alrasyid (ADISAM PUBLISHER, 2024)
This article aims to discuss the miracles of the Qur'an or l'jaz al-Qur'an in the uslub Al Qur'an in the form of Hamzah istifham which is part of i'jaz Al Bayani. The writing method used is a qualitative method in data collection techniques using library research analysis methods. The data collection method involves literature study of the Qur'an and related literature. The novelty of this research is the application of the concept of i'jaz Al Bayani in understanding the meaning of the language of the Qur'an, providing deeper insight into linguistic phenomena in the sacred text. Thus, this research makes an important contribution in understanding the richness of the language of the Qur'an and its relevance in linguistic and literary contexts. The beauty of the language of the Koran was born as a challenge to the Arab people at that time to match it. Balagbab science as a scientific discipline that studies the beauty of language, in it discusses istifham (questions) which are included in the study of kalam insha'i.